Analisis Daya Dukung Konservasi Pada Ekowisata Kebun Raya Baturraden di Banyumas - Kumala Dewi; Moh. Husein Sastranegara; Endang Hilmi (Pascasarjana Universitas Jenderal Soedirman, 2022)
The Baturraden Botanical Garden is one of the developing destinations in Banyumas, and the increase can see this in visitors. The presence of visitors with all their activities will affect environmental conditions, so proper management is needed to reduce the negative impacts but can still provide visitors comfort and satisfaction. This study aims to determine the carrying capacity of ecotourism conservation in Baturraden Botanical Garden. The analysis technique to obtain carrying capacity is based on the modified Cifuentes formula (1992), consisting of physical carrying capacity/PCC, real carrying capacity/RCC, and effective carrying capacity/ECC. The method used the quantitative descriptive method, observation, questionnaires, interviews, and literature studies to collect data. The formulation of the development strategy was carried out utilizing SWOT analysis. The results of the calculation obtained a PCC value of 28,697 visitors/day/5,175 ha, an RCC value of 107 visitors/day/5,175 ha, an ECC value of 86 visitors/day/5,175 ha. The value of the conservation carrying capacity of the Baturraden Botanical Garden is currently not exceeded, can still accommodate visitors without causing environmental damage, and can be well served by the manager.